2022
DOI: 10.3389/fmolb.2022.841223
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and the Role of Metabolites in the Study of Graves’ Disease

Abstract: Graves’ disease (GD) is an autoimmune thyroid disease (AITD), which is one of the most common organ-specific autoimmune disorders with an increasing prevalence worldwide. But the etiology of GD is still unclear. A growing number of studies show correlations between gut microbiota and GD. The dysbiosis of gut microbiota may be the reason for the development of GD by modulating the immune system. Metabolites act as mediators or modulators between gut microbiota and thyroid. The purpose of this review is to summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 120 publications
(155 reference statements)
0
7
0
Order By: Relevance
“…revealed that the Firmicutes -to- Bacteroidetes ratio was decreased in individuals with GD, which suggested that the gut microbiome may participate in the pathogenesis of GD ( 12 ). However, the generalization of the findings or ability to make a definitive conclusion was limited owing to the small number of fecal samples evaluated ( 13 ). In addition to clinical research, basic medical research has also provided evidence on the TGA.…”
Section: Introductionmentioning
confidence: 99%
“…revealed that the Firmicutes -to- Bacteroidetes ratio was decreased in individuals with GD, which suggested that the gut microbiome may participate in the pathogenesis of GD ( 12 ). However, the generalization of the findings or ability to make a definitive conclusion was limited owing to the small number of fecal samples evaluated ( 13 ). In addition to clinical research, basic medical research has also provided evidence on the TGA.…”
Section: Introductionmentioning
confidence: 99%
“…These compositional changes can lead to dysbiosis and the consequent disturbance of human health. As follows, microbiota imbalance has been associated with autoimmune and inflammatory disorders (inflammatory bowel disease, asthma, allergies) and with the acceleration of chronic diseases such as cardiovascular disease, obesity, diabetes or cancer ( Wilkins et al, 2019 ; Miller et al, 2021 ; Liu et al, 2022 ). Also, several recent studies have identified microbiota dysbiosis in patients affected by different neurodegenerative diseases pointing to a possible connection between the gut microbiota and the origin of neurological disorders ( Figure 1 ) ( Rogers et al, 2016 ; Friedland and Chapman, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results from a European study seem to be significantly different. Even more heterogeneous are the results regarding lower taxonomic levels [ 14 , 16 , 23 , 26 , 32 34 , 36 38 , 41 , 43 , 44 , 48 ] Is there a variation in microbiota composition in patients with thyroid cancer? The very few studies available seem to indicate the reduction of the butyrate-producing gut microbiota as potential signature of thyroid cancer.…”
Section: Resultsmentioning
confidence: 99%